Kairo, Ägypten. Die Goldblechbeschläge aus dem Grab des Tutanchamun - Bertsch, Julia; Broschat, Katja; Eckmann, Christian (e-Forschungsberichte des DAI, 2017)
Apart from the ongoing restauration of the gold sheet appliqués from the tomb of Tutankhamun, several important studies could be accomplished as part of the joint German-Egyptian project. The iconographical analysis which is nearly completed deals with both traditional Egyptian and ‘international’ motifs depicted on the gold sheets and how they were integrated in the context of Egyptian art at the end of the 18th dynasty. Furthermore, various technical aspects concerning the backings of the gold sheets which consist of different layers of leather, textile, gesso and resins were investigated. In addition, the composition of the gold was examined by portable XRF-analysis resulting in the identification of six different material groups which broadly overlap with groups formed on grounds of iconographical results.